The interrelationship between internal marketing, employee perceived quality and customer satisfaction: A conventional banking perspective - Leigh De Bruin; Mornay Roberts-Lombard; Christine De Meyer-Heydenrych (Cogent Business & Management, 2021)
This study explores how internal marketing influences employees' perceived ability to deliver service quality in the conventional banking industry in Oman. The influence of employee perceived service quality on customer satisfaction is also established. Data was obtained from retail banking branch employees at the customer front line of conventional banks in Oman using electronic surveys. A total of 355 responses were obtained for data analysis. The measurement and structural models were measured through structural equation modelling. The findings reveal that internal price, internal promotion, and internal performance management are influencers of service quality, with the latter having a direct relationship with customer satisfaction. In addition, service quality has a positive influence on customer satisfaction in conventional banks in Oman. The findings can guide conventional banking management in Oman on how internal marketing can promote service quality, ultimately leading to positive customer satisfaction experiences. Internal marketing as a strategy has been explored mostly in established western markets and not in the Middle Eastern region of the world. This study explores different internal marketing mix elements, which have been tested for the enablement of service quality and customer satisfaction in the conventional banking sector of Oman.
Keywords: 650; internal marketing; service quality; customer satisfaction; conventional banking; frontier marke